Recent progress in the development of steroid sulphatase inhibitors – examples of the novel and most promising compounds from the last decade. (1st January 2020) - Daśko, Mateusz; Demkowicz, Sebastian; Biernacki, Karol; Ciupak, Olga; Kozak, Witold; Masłyk, Maciej; Rachon, Janusz
Abstract: The purpose of this review article is to provide an overview of recent achievements in the synthesis of novel steroid sulphatase (STS) inhibitors. STS is a crucial enzyme in the biosynthesis of active hormones (including oestrogens and androgens) and, therefore, represents an extremely attractive molecular target for the development of hormone-dependent cancer therapies. The inhibition of STS may effectively reduce the availability of active hormones for cancer cells, causing a positive therapeutic effect. Herein, we report examples of novel STS inhibitors based on steroidal and nonsteroidal cores that contain various functional groups (e.g. sulphamate and phosphorus moieties) and halogen atoms, which may potentially be used in therapies for hormone-dependent cancers. The presented work also includes examples of multitargeting agents with STS inhibitory activities. Furthermore, the fundamental discoveries in the development of the most promising drug candidates exhibiting STS inhibitory activities are highlighted.